1991
DOI: 10.1161/01.cir.84.5.2063
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic effects of tranexamic acid and desmopressin during cardiac surgery.

Abstract: Desmopressin exerts no hemostatic effect, with or without prior administration of antifibrinolytic drug. Prophylactic tranexamic acid alone appears economical and safe in decreasing blood loss and transfusion requirement after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(107 citation statements)
references
References 43 publications
3
102
0
2
Order By: Relevance
“…Long-term follow-up data on these patients was not available, however, the remote thromboembolism secondary to intraoperative single dose of tranexamic acid seems unlikely as it has a short halflife (14) . This observation is in accordance with other controlled studies; including several randomised studies in patients undergoing cardiac surgery (43)(44)(45)(46) . Furthermore, no thromboembolic episode was reported in a retrospective analysis of 256 pregnant women with bleeding disorders who were on tranexamic acid (47) .…”
Section: Surgical Field Qualitysupporting
confidence: 92%
“…Long-term follow-up data on these patients was not available, however, the remote thromboembolism secondary to intraoperative single dose of tranexamic acid seems unlikely as it has a short halflife (14) . This observation is in accordance with other controlled studies; including several randomised studies in patients undergoing cardiac surgery (43)(44)(45)(46) . Furthermore, no thromboembolic episode was reported in a retrospective analysis of 256 pregnant women with bleeding disorders who were on tranexamic acid (47) .…”
Section: Surgical Field Qualitysupporting
confidence: 92%
“…Moreover, a few direct comparison studies [56,57] and a metaanalysis [58] on blood-saving agents in cardiac surgery have shown that other nontransfusional hemostatic agents such as aprotinin, tranexamic acid, and e-aminocaproic acid are more effective than DDAVP. There are few clinical trials evaluating the prophylactic use of DDAVP in noncardiac surgery.…”
Section: Desmopressin In Patients Without Preexisting Bleeding Disordersmentioning
confidence: 99%
“…Subsequent trials have failed to show a reduction in blood loss following DDAVP administration. Horrow et al were able to show that co-administration of TXA was necessary in a small group of patients to reduce blood loss, which the authors attributed to concomitant tissue plasminogen activator release [63].…”
Section: Desmopressinmentioning
confidence: 99%